Genome-wide association meta-analysis yields 20 loci associated with gallstone disease - Egil Ferkingstad (Nature Portfolio, 2018)
Genome-wide association studies have so far identified eight risk loci for gallstone disease. Here, the authors perform meta-analysis in cohorts from Iceland and the UK which reveals further 21 common and low-frequency risk variants that highlight the role of bile acid homeostasis in gallstone disease.